Simultaneous Contact and Grain‐Boundary Passivation in Planar Perovskite Solar Cells Using SnO2‐KCl Composite Electron Transport Layer. Issue 3 (5th December 2019) - Zhu, Pengchen; Gu, Shuai; Luo, Xin; Gao, Yuan; Li, Songlin; Zhu, Jia; Tan, Hairen
Abstract: The performance of perovskite solar cells is sensitive to detrimental defects, which are prone to accumulate at the interfaces and grain boundaries of bulk perovskite films. Defect passivation at each region will lead to reduced trap density and thus less nonradiative recombination loss. However, it is challenging to passivate defects at both the grain boundaries and the bottom charge transport layer/perovskite interface, mainly due to the solvent incompatibility and complexity in perovskite formation. Here SnO2 ‐KCl composite electron transport layer (ETL) is utilized in planar perovskite solar cells to simultaneously passivate the defects at the ETL/perovskite interface and the grain boundaries of perovskite film. The K and Cl ions at the ETL/perovskite interface passivate the ETL/perovskite contact. Meanwhile, K ions from the ETL can diffuse through the perovskite film and passivate the grain boundaries. An enhancement of open‐circuit voltage from 1.077 to 1.137 V and a corresponding power conversion efficiency increasing from 20.2% to 22.2% are achieved for the devices using SnO2 ‐KCl composite ETL. The composite ETL strategy reported herein provides an avenue for defect passivation to further increase the efficiency of perovskite solar cells. Abstract : This study reports a simultaneous contact and grain‐boundary passivation strategy in planar perovskite solar cells using SnO2 ‐KCl composite as the electron transport layer. When applied to perovskite solar cells employing a composition of (FAPbI3 )0.95 (MAPbBr3 )0.05, this strategy increases the open‐circuit voltage from 1.077 to 1.137 V and the corresponding efficiency from 20.2% to 22.2%.